Comparison of Short and Long-Term Outcomes of Metabolic and Bariatric Surgery in Adolescents and Adults - Stanford, Fatima Cody; Mushannen, Tasnim; Cortez, Priscilla; Campoverde Reyes, Karen J.; Lee, Hang; Gee, Denise W.; Pratt, Janey S.; Boepple, Paul A.; Bredella, Miriam A.; Misra, Madhusmita; Singhal, Vibha (Frontiers in Endocrinology, 2020)
Objective: We sought to compare the short and long-term outcomes of MBS in adolescents vs. adults who have undergone a Roux-en-Y gastric bypass (RYGB) or Sleeve gastrectomy (SG). Design: Retrospective Cohort Study Setting: Single tertiary care academic referral center Participants: 150 adolescent (≤21-years) and adult (>21-years) subjects with severe obesity between 15-70 years of age who underwent RYGB or SG. Outcomes: Metabolic parameters, weight and height measures were obtained pre-and post-surgery (at 3 and 6 months, and then annually for 4 years). Results: Median pre-surgical body mass index (BMI) was higher in adolescents (n=76) vs. adults (n=74): 50 (45–57) vs. 44 (40–51) kg/m2 (p<0.0001). However, obesity related complications were greater in adults vs. adolescents: 66% vs. 21% had hypertension, 68% vs. 28% had dyslipidemia, and 42% vs. 21% had type 2 diabetes mellitus (all p<0.010). % BMI reduction and % weight loss (WL) were greater in adolescents vs. adults at all time points (p<0.050). %WL was higher in adolescents who underwent SG at each time point (p<0.050), and trended higher among adolescents who underwent RYGB (p=0.060), compared to adults with the respective procedure. Follow-up data showed greater resolution of type 2 diabetes and hypertension in adolescents than adults (87.5 vs. 54.8%; p=0.04, and 68.7 vs. 35.4%; p=0.040). Conclusion: Adolescents compared to adults had greater reductions in BMI and weight, even at 4 years, and greater resolution of type 2 diabetes and hypertension. Earlier intervention in the treatment of severe obesity with MBS may lead to better outcomes.